Adequacy of the local government financial reporting model in the context of internal decision-making: an exploratory study in the municipality of Bragança - Nogueira, Sónia P. (2013)
This paper addresses the adequacy of the Local Government financial reporting model for internal decision-making by developing an exploratory empirical study that evaluates internal users’ satisfaction concerning the reporting model within the municipality of Bragança. It additionally examines to what extent internal control and financial reporting information opportunity are important for municipalities’ internal decision-making. In Portugal important developments have recently emerged in public sector accounting systems in the context of internal decision-making and control, hence calling for further studying Local Government current financial reporting model in this context. From an experimental questionnaire applied to decision-makers of Bragança municipality in 2010, main findings show that the actual reporting model is not the most appropriate in providing information for internal decision-making in that municipality. Moreover, both internal control and opportunity of the financial reporting information seem to have significant importance in the context of internal decision-making.